Wise Administrative Leadership and Its Role in Developing Positive Organizational Behavior among Administrative Employees - BELAIDOUNI, Lakhdar; FELLAHI, Billel (Journal of Human Sciences, 2025)
Management in organizations faces significant challenges in achieving quality, stability, and sustainability. Leaders, therefore, bear the responsibility of fostering an effective organizational climate that combines the art and science of guiding human behavior in the workplace. Administrative leadership is not merely a position; it is a duty that necessitates decision-making and efficient resource management. A successful leader must possess essential qualities and skills to manage individuals effectively. Wise leadership is crucial for maximizing the potential of human resources, as it directly influences key organizational functions such as planning, organizing, coordinating, and directing, driving institutional growth and resilience. Furthermore, wise leadership enhances institutional sustainability by fostering employee commitment and loyalty. By creating a collaborative and supportive environment, leadership becomes a cornerstone for achieving organizational goals, adapting to current challenges, and ensuring institutional stability and excellence.